Sea of Monsters: Percy Jackson & the Olympians #2 - Freudenthal, Thor; Lerman, Logan, 1992-; Jackson, Brandon T., 1984-; Daddario, Alexandra, 1986-; Lockington, Andrew, 1974-; Riordan, Rick. (Beverly Hills, Calif. : Twentieth Century Fox Home Entertainment, 2013)
Joined by his friends and half brother, Percy journeys to the Sea of Monsters to retrieve the Golden Fleece and save Camp Half-Blood.
Originally released as a motion picture in 2013.
Based on the novel "Percy Jackson and the Olympians. The sea of monsters" by Rick Riordan.
Sequel to "Percy Jackson & the lightning thief" (2010).
Dolby digital 5.1, wide screen 2.40:1.
Features: Back to Camp Half-Blood, It's all in the eye, theatrical trailers.
Director of photography, Shelly Johnson ; production design, Claude Paré ; editor, Mark Goldblatt ; music, Andrew Lockington.
Keywords: Riordan, Rick -- Film adaptations; Jackson, Percy (Fictitious character) -- Drama; Quests (Expeditions) -- Drama; Mythology, Greek -- Drama; Gods, Greek -- Drama; Action and adventure films; Fiction films; Video recordings for the hearing impaired; Based on the book; Feature films; Fantasy films